Noise problems in air conditioning installations - Barkawi, Sahari, Prof. Dr.; Nor Mariah, Adam, Prof. Dr.; Decruz, Aloysius (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/